Engineering G-quadruplex DNA : a combined computational and experimental study - Lech, Christopher Jacques (2014)
G-quadruplex nucleic acids have received a great deal of research attention for their biological functions, therapeutic potential, and roles in nanotechnology. The research focus of this thesis is dedicated to the engineering of G-quadruplex DNA structures. We approach this problem through a combination of experimental and computational approaches. We examine some of the fundamental interactions that govern G-quadruplex structure and their high order assemblies. In addition, we investigate the effects of G-quadruplex geometry on electronic conductance of stacked G-tetrads. A large part of our research efforts deal with the development and application of alternative nucleic acid chemistries within G-quadruplex structures. These include chemical modifications to the guanine base and to the sugar moiety of the backbone. We demonstrate how these chemical tools may be used to enhance some beneficial properties G-quadruplexes and to rationally design stable and functionalizable G-quadruplex nanoparticles for applications in nanotechnology and therapeutics